Interpreting non-clinical toxicity studies in psychiatric drug development: human relevance and safety - Mandelblat-Cerf, Yael (Henry Stewart Talks, 2026)
Psychiatric drug development, Challenges in early drug development, Challenges associated with lifelong treatment, Non-clinical toxicity studies, Toxicity studies for psychiatric therapeutics, Relevance to human safety